The Tragedy of Doctor Faustus: Between Forbidden Pleasures and the Torment of Consequences - An Analytical and Philosophical Study. - mohammed waleed asaad, Asst. Lect. (lark, 2025)
This paper offers an examination of Doctor Faustus and explores the various dimensions of the tragedy, focusing particularly on the ascent and total immersion in desires and pleasures, followed by the downfall and the unavoidable dreadful conclusion. And the philosophical aspect behind it. Marlowe is acknowledged as a prominent playwright in tragic drama during the Elizabethan period. The paper highlights how Marlowe’s unique style of crafting tragedy distinguishes him from other dramatists of his era. This study delves into multiple facets of the tragedy and imparts the moral that humanity should never defy divine will, as well as the inevitable consequences of a misguided path. Even those with extensive education should avoid the arrogance tied to power and wisdom. The pursuit of authority and knowledge must ultimately serve the greater good of humanity; otherwise, one may encounter severe repercussions, as starkly illustrated by the tragic fate of the esteemed scholar, Doctor Faustus.
Keywords: Doctor Faustus, Passion, Power, Knowledge